Pump performance evaluation through total different head and power - Azman Jamaludin, 1969-, author 635365 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2020)
Thesis (Sarjana Falsafah, Bidang Penyelidikan : Kejuruteraan Mekanikal)